Distance learning: a proposal for improving bioethical education - Carvalho, Fernanda T.; Muller, Marisa C.; Ramos, Mauro C. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Distance learning (DL) has shown to be an interesting educational alternative. Current technologies grant the use of Internet for teaching and learn-ing. Its interactivity made possible a very close relationship between teacher and student. Considering the great need of improving the knowledge of Bioethics, DL can be a very useful tool to reach a large number of health professionals at low cost. This paper presents a proposal for a course on the basics of Bioethics aimed at health students, professionals and researchers. It is a free of charge, short course that intends to stimulate the study of Bioethics and will be considered a requisite in order to take other health courses on our institution. An advantage of such methodology is to provideautonomy to students. DL focuses on writing and reading skills, which is very important on education of health students.